Administrative-Operational Mismatch in Electoral Policy Implementation: Evidence from Independent Candidate Verification in Gorontalo - Fahruddin Umar; Rauf Hatu; Yakob Noho Nani; Yanti Aneta; Fenti P. Dance Tui (Lembaga Riset Ilmiah, 2026)
This article examines the administrative-operational gap in the implementation of the factual verification policy of independent regional head candidates in Gorontalo City, Indonesia. Different from the election governance literature that tends to emphasize procedural compliance, institutional integrity, and regulatory accountability, this article explains how implementation contradictions arise in highly procedurally organized systems. For this reason, this study developed an Administrative–Operational Reflective Governance Model (AORGM) as a conceptual framework to understand institutional adaptation to the operational complexity of election verification. Using an analytical-conceptual design, this article combines a synthesis of governance literature, policy analysis, institutional documents, and empirical evidence of selective coding results of implementation findings. The analytical framework integrates implementation theory, administrative burden, street-level bureaucracy, and reflective governance to explain the recursive relationship between policy formalization, field adaptation, socio-cultural context, and institutional learning. The findings suggest that implementation contradictions do not primarily stem from formal procedural failures, but rather from operational pressures that go beyond the adaptive capacity of institutions. Although verification targets are achieved, the implementation process results in hidden administrative burdens, officer burnout, technological instability, social tension, and adaptive informal practices. The study identifies four dimensions of reflexivity: moral, epistemic, analytical, and institutional. AORGM contributes by positioning the implementation gap as a reflective governance phenomenon, not just an administrative technical problem